Changes in serum levels of miR-21, miR-210, and miR-373 in HER2-positive breast cancer patients undergoing neoadjuvant therapy: a translational research project within the Geparquinto trial - Mueller, Volkmar; Gade, Stephan; Steinbach, Bettina; Loibl, Sibylle; Von Minckwitz, Gunter; Untch, Michael; Schwedler, Kathrin; Luebbe, Kristina; Schem, Christian; Fasching, Peter; Mau, Christine; Pantel, Klaus; et al. (Breast Cancer Research and Treatment, 2014)
Trastuzumab and lapatinib are established treatments for patients with HER2 (human epidermal growth factor receptor 2)-positive breast cancer with different mechanisms of action. The focus of this study is to investigate, whether altered expression levels of potentially relevant microRNAs (miRs) in serum are associated with response to trastuzumab or lapatinib. Circulating miR-21, miR-210, and miR-373 were quantified with TaqMan MicroRNA assays in serum of 127 HER2-postive breast cancer patients before and after neoadjuvant therapy and in 19 healthy controls. Patients received chemotherapy combined with either trastuzumab or lapatinib within the prospectively randomized Geparquinto trial. The association between miR levels and pathological response (pCR) to therapy and type of therapy was examined. Serum levels of miR-21 (p = 5.04e-08, p = 1.43e-10), miR-210 (p = 0.00151, p = 1.6e-05), and miR-373 (p = 7.87e-06, p = 1.75e-07) were significantly higher in patients before and after chemotherapy than in healthy women. Concentrations of miR-21 (p = 5.73e-08), miR-210 (p = 0.000724), and miR-373 (p = 0.00209) increased further after chemotherapy. A significant association of higher serum levels of miR-373 with advanced clinical tumor stage could be detected (p < 0.002). An association of miR-21 levels before (p = 0.0091) and after (p = 0.037) chemotherapy with overall survival of the patients could be detected, independent of type of anti-HER2 therapy. No association of circulating miRs with pCR was found. Our findings demonstrate a specific influence of neoadjuvant therapy on the serum levels of miR-21, miR-210, and miR-373 in breast cancer patients together with a prognostic value of miR-21.
EVALuna2:17515